Characterizing social conflict over wolf reintroduction in Colorado: A theoretical model of intergroup conflict - Mireille N. Gonzalez; Taylor N. Heid; Rebecca Niemiec (People and Nature, 2024)
Abstract Context: Wolf restoration is a highly divisive issue in the American West, with stakeholder conflict driven by value and identity‐based disagreements. Research suggests that such conflicts require reconciliation to repair intergroup relations before negotiations to address the issue can begin, yet, in the conservation and natural resource management fields, stakeholder processes about divisive issues typically focus only on negotiations. There is a gap in the literature on how to identify and target the drivers of value and identity‐based conflicts. Approach: We interviewed stakeholders highly engaged in the issue of proposed wolf reintroduction in Colorado to gain insight on the drivers of the conflict and to inform reconciliation interventions. We pulled from conflict and peace‐building theories to frame our analysis, specifically suggestions that conflict is fueled by four categories of perceptions, including perceptions of: the group one is in conflict with, one's own social group, the relationship between groups, and the nature of the conflict. Key Findings: We found that all interviewees discussed perceptions that can fuel conflict within each of these four categories. However, interviewees who identified as 3rd parties to the conflict primarily discussed the relationships between those in conflict and engaged in thoughtful perspective‐taking, an activity that can help reduce conflict. Conversely, both those strongly in support of reintroduction and strongly opposed to reintroduction most commonly described negative perceptions about individuals they are in conflict with and positive perceptions about themselves and their social group. For example, when discussing others, both groups described each other as acting in unjust and unfair ways, as being incapable of or unwilling to change, and as misinformed. When describing positive perceptions of themselves, both those in support and those in opposition viewed their own goals as just and themselves as victims of outgroup members’ actions. Synthesis and applications: Based on our findings, we suggest various reconciliation interventions that may assist wildlife managers in reducing the conflict about wolf reintroduction in Colorado. These recommendations may also be applicable to wildlife managers working on other issues with high stakeholder conflict. Read the free Plain Language Summary for this article on the Journal blog.